Disseminated histoplasmosis presenting as pelvic inflammatory disease. Issue 1 (27th November 2015) - Rimtepathip, Parin P.; Erickson, Alex; Katner, Harold; Bakri, Younes
Key Clinical Message: A 39‐year‐old female patient was presented with acute abdominal pain. Diagnostic laparoscopy revealed extensive granulomas throughout the abdomen. Disseminated TB was suspected, but the biopsies were negative. Due to a high degree of suspicion, a urine antigen test was performed and was strongly positive for histoplasmosis. Abstract : A 39‐year‐old female patient was presented with acute abdominal pain. Diagnostic laparoscopy revealed extensive granulomas throughout the abdomen. Disseminated TB was suspected, but the biopsies were negative. Due to a high degree of suspicion, a urine antigen test was performed and was strongly positive for histoplasmosis.